2014
DOI: 10.1007/s00404-014-3548-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mefenamic acid and ginger on pain relief in primary dysmenorrhea: a randomized clinical trial

Abstract: Ginger is as effective as mefenamic acid on pain relief in primary dysmenorrhea. Ginger does not have adverse effects and is an alternative treatment for primary dysmenorrhea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 28 publications
(45 reference statements)
1
65
0
6
Order By: Relevance
“…Finally, 7 RCTs met the inclusion criteria after removing 3 non-RCT studies (Figure 1). The 7 RCTs were used for the systematic review [23][24][25][26][27][28][29]. The main data from included RCTs were summarized in Table 1.…”
Section: Summary Of Included Studiesmentioning
confidence: 99%
“…Finally, 7 RCTs met the inclusion criteria after removing 3 non-RCT studies (Figure 1). The 7 RCTs were used for the systematic review [23][24][25][26][27][28][29]. The main data from included RCTs were summarized in Table 1.…”
Section: Summary Of Included Studiesmentioning
confidence: 99%
“…In a clinical trial by Shirvani et al (2015), the effect of ginger on dysmenorrhea was demonstrated. The cause of pain from primary dysmenorrhea is uterine contraction and ischemia as a result of the excessive production of prostaglandins in the endometrium during ovulation.…”
Section: Discussionmentioning
confidence: 99%
“…Ginger compounds include various substances, such as gingerols, gingerdiones, beta carotene, capsaicin, caffeic acid, and curcumin. The effect of ginger on dysmenorrhea occurs via its gingerol and gingerdione compounds (Shirvani et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Zu einem ähnlichen Resultat gelangten Shiravani et al [34], die in einer RCT-Vergleichsstudie die Wirksamkeit von Ingwer (4 × 250 mg/Tag) mit Mefenaminsäure (3 × 250 mg/Tag) verglichen. Ingwer erwies sich also ebenso wirksam zur Behandlung von Dysmenorrhö wie das Standardpräparat Mefenaminsäure.…”
Section: Klinische Studien 2013-2015: Menstruationsproblemeunclassified